Introdução a uma clínica da simpatia - Zasso, Mariel Rosauro (2010)
This essay talks about theoretical devices with which we can operate relations of sympathy in clinical encounters. We propose to highlight the complexity of the issue through a brief overview of what happened with the idea of sympathy throughout the history of Western thought. From the viewpoint of conceptual connections, we rely especially to David Hume, for whom, in the eighteenth century, the issue that influences the theme of sympathy is that of relations between humans. Because sympathy is a passion, and like all passion, in Hume, is characterized by its partiality, the difficulty to consider, in the social point of view, is the sympathy's intensity reduccion as it extends. A sympathy's clinic is thematized in resonance with this problem, discussed with help of Gilles Deleuze's book Empirisme et subjectivité (1953). This clinical practice should promote the intensification of sympathy without recreate the relational limitation that it suffers from restricted groups, like family, and be able to establish itself as a nomadic place of relations of sympathy's extent, in favor of an affirmation of differential life